Upper Endoscopy for GI Fellows - Adler, Douglas G. (Springer International Publishing : Imprint: Springer, 2017)
This volume provides a concise overview of the most important and vital aspects of upper endoscopy. The text is specifically geared towards first-year GI fellows and novice endoscopists in order to help them rapidly assimilate the core concepts needed to perform upper endoscopy in the most important and most commonly encountered clinical situations. The book also covers the most important variations of normal anatomy and pathology and how to manage them. Key concepts covered include foreign body removal, diagnosis and management of upper GI bleeding, Barrett's Esophagus, evaluation and management of benign and malignant strictures of the esophagus, stomach, and duodenum, submucosal lesions, and evaluation of post operative upper GI anatomy. A plethora of high quality color illustrations and narrated online video clips illustrate major concepts in the book are also included. Written by experts in the field, Upper Endoscopy for GI Fellows is a valuable resource for new physicians just starting to perform upper endoscopy. .
Keywords: Medicine.; Gastroenterology.; elektronické knihy; electronic books